A competitive study of the level of functional commitment between males and females of physical education teachers in the Baghdad education Directoratel/ AL-karkh and AL-Rusafa - م.د. شذى عبد الحافظ اسماعيل (الرياضة المعاصرة)
The teacher’s behavior emerges as an additional behavior in the positive effects that are reflected on the organizations as it creates interaction between school members and enhances their affiliation with the educational institution and raises their level of job commitment as it raises their morale and their productivity in performance that contributes to achieving the goals of the institution and therefore it is important of the job commitment to improve the job performance of teachers And physical education teachers, and the research aims to identify the level of job commitment of teachers and teachers of physical education in the education of karkh and Rusafa, the researcher used the descriptive approach and the research sample consisted of (540) teachers and schools, and used For the researcher of the questionnaire form as a tool for evaluating the level of job commitment to collect data, the results of the overall result of the level of job commitment in the fields as a whole were high, the percentage of response to them reached about (73%) .The researcher also recommends showing the achievements of teachers and teachers and their creativity and appreciation certificates obtained by the school In a prominent place inside the school.